2012
DOI: 10.1007/s10278-012-9550-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Computer-Aided Detection in Very Small Screening Detected Invasive Breast Cancers

Abstract: This study aims to assess computer-aided detection (CAD) performance with full-field digital mammography (FFDM) in very small (equal to or less than 1 cm) invasive breast cancers. Sixty-eight invasive breast cancers less than or equal to 1 cm were retrospectively studied. All cases were detected with FFDM in women aged 49-69 years from our breast cancer screening program. Radiological characteristics of lesions following BI-RADS descriptors were recorded and compared with CAD sensitivity. Age, size, BI-RADS cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…þ β 4 ðBI − RADS ij ¼ 1Þ þ β 5 ðdensity ij ¼ "Extremely"Þ þ β 6 ðdensity ij ¼ "Heterogeneous"Þ þ β 7 ðdensity ij ¼ "Fibroglandular"Þ þ ε ij ; (1) where "ln" is the natural logarithmic function; β 0i is the intercept term for reader i; CAD ij is the number of CAD marks with corresponding reader-specific coefficient β 1i ; images ij is the number of images; BI-RADS ij is the BIRADS category where, e.g., ðBI-RADS ij ¼ 0Þ is an indicator variable that takes the value 1 if BI-RADS ij ¼ 0 and otherwise is 0; density ij is the breast density category; and ε ij is the error term. We assume that the ðβ 0i ; β 1i Þ pairs have a bivariate normal distribution across readers with means β 0 and β 1 , variances σ 2 β 0i and σ 2 β 1i , and covariance σ β 0 β 1 , and we assume that the ε ij are independent and normally distributed with zero mean and variance σ 2 ε . Note that only the intercept and CAD coefficient vary across readers; i.e., for the other independent variables, the corresponding regression coefficients are assumed constant across readers.…”
Section: Specification Of the Mixed Linear Regression Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…þ β 4 ðBI − RADS ij ¼ 1Þ þ β 5 ðdensity ij ¼ "Extremely"Þ þ β 6 ðdensity ij ¼ "Heterogeneous"Þ þ β 7 ðdensity ij ¼ "Fibroglandular"Þ þ ε ij ; (1) where "ln" is the natural logarithmic function; β 0i is the intercept term for reader i; CAD ij is the number of CAD marks with corresponding reader-specific coefficient β 1i ; images ij is the number of images; BI-RADS ij is the BIRADS category where, e.g., ðBI-RADS ij ¼ 0Þ is an indicator variable that takes the value 1 if BI-RADS ij ¼ 0 and otherwise is 0; density ij is the breast density category; and ε ij is the error term. We assume that the ðβ 0i ; β 1i Þ pairs have a bivariate normal distribution across readers with means β 0 and β 1 , variances σ 2 β 0i and σ 2 β 1i , and covariance σ β 0 β 1 , and we assume that the ε ij are independent and normally distributed with zero mean and variance σ 2 ε . Note that only the intercept and CAD coefficient vary across readers; i.e., for the other independent variables, the corresponding regression coefficients are assumed constant across readers.…”
Section: Specification Of the Mixed Linear Regression Modelmentioning
confidence: 99%
“…CAD is notorious for creating a large number of false-positive marks. 2 4 Its overall value in screening has been questioned, with a study in 2011 finding that in a large cohort of women undergoing screening mammography, the use of CAD decreased specificity for breast cancer detection but did not have a statistically significant improvement in detection rate or decrease in breast cancer stage, size, or nodal status. 5 A later study by an overlapping group of authors of another large cohort of patients showed CAD to increase detection of ductal carcinoma in situ and to allow detection of invasive breast cancer at earlier stages.…”
Section: Introductionmentioning
confidence: 99%